2015
DOI: 10.1088/0963-0252/24/2/025038
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of a cold atmospheric pressure plasma jet through a long flexible plastic tube

Abstract: This work proposes an experimental configuration for the generation of a cold atmospheric pressure plasma jet at the downstream end of a long flexible plastic tube. The device consists of a cylindrical dielectric chamber where an insulated metal rod that serves as high-voltage electrode is inserted. The chamber is connected to a long (up to 4 m) commercial flexible plastic tube, equipped with a thin floating Cu wire. The wire penetrates a few mm inside the discharge chamber, passes freely (with no special supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 33 publications
2
41
0
Order By: Relevance
“…Hence, the generation of non‐equilibrium diffuse plasma under atmospheric pressure is the next technical challenge. Although this can be relatively easily circumvented by the use of noble gas such as argon or helium, that significantly increases the plasma uniformity . Eventually the price of the gas can have a negative economic aspect to potential production process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the generation of non‐equilibrium diffuse plasma under atmospheric pressure is the next technical challenge. Although this can be relatively easily circumvented by the use of noble gas such as argon or helium, that significantly increases the plasma uniformity . Eventually the price of the gas can have a negative economic aspect to potential production process.…”
Section: Introductionmentioning
confidence: 99%
“…Although this can be relatively easily circumvented by the use of noble gas such as argon or helium, that significantly increases the plasma uniformity. [8][9][10] Eventually the price of the gas can have a negative economic aspect to potential production process.…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors did not report the length of their extension tube. Using a similar setup (a long plastic tube with floating electrode connected to a coaxial DBD reactor) the authors in ref . observed that the plasma did not propagate along the pipe but instead a plasma jet could be generated at the tube exit.…”
Section: Introductionmentioning
confidence: 99%
“…This method can be applied for different geometry of the primary plasma, several working gases (He, Ar, and some mixtures were tested), and also for tubes as long as 4.0 m. Since the primary DBD and the plasma jet are connected in series, the total discharge power is set by the primary discharge and thus the current and the power of the plasma jet are limited. Due to its suppressed power, the plasma jet obtained by this method is cold enough to be put in direct contact with human skin . Moreover, the plastic tube end can be held by hand without electric shock and the plasma jet can be easily manipulated and directed on a target.…”
Section: Introductionmentioning
confidence: 99%
“…Aiming to be specifically and locally delivered, such technology drives the plasma up to the target where the plasma is transferred in ambient air at the outlet of the capillary. However, there are few reports dealing with the TP or in other words, propagation of IW through a dielectric tube [20][21][22][23], and the mechanisms about the formation of ionization waves inside a dielectric tube still remain unclear. Especially, the effect of electrode structure on the propagation of IW through long dielectric tube needs to be further investigated.…”
Section: Introductionmentioning
confidence: 99%